Development of complex-structure ore deposits by means of chamber systems under conditions of the Kryvyi Rih iron ore field - Pysmennyi, Serhii; Brovko, Dmytro; Shwager, Natalya; Kasatkina, Iryna; Paraniuk, Dmitriy; Serdiuk, Oleksandra (Eastern-European Journal of Enterprise Technologies, 2018)
In order to keep their positions in the world markets, mining enterprises of the Kryvyi Rih iron ore field using the deep-mine method need to develop a resource-saving technology for the development of the fields represented by complex-structure ore deposits. Development of the resource-saving technology must be carried out at the initial stage which is directly related to ore extraction and affects content of iron in the extracted ore mass. Growth of iron content in the extracted ore mass can be achieved through the use of selective development of the extraction blocks by means of the chamber development systems. The existing procedure of determining structural components of the chamber system of development applied at the Kryvbas mines does not take into account thickness of the overlying strata on the side of the hanging wall of the cleaning chamber when calculating the exposure strike. Therefore, it is necessary to improve the procedure for determining the structural components of the chamber system of development when working out complex ore fields, in order to obtain high extraction rates. For the development of the extraction block, it was suggested to carry out the cleaning works sequentially from the hanging to the lying wall of the complex-structure ore field with the use of the chamber system of development with leaving the non-ore or ore-containing inclusion in the pillar. This sequence of cleaning will reduce concentration of tensile and compressive stresses in the middle part of the non-ore or ore-containing inclusion which will contribute to a 1.5‒2.0-time increase in its stability. It has been established that stability of the cleaning chamber, in addition to its dimensions and physico-mechanical properties of the ore, is influenced by horizontal thickness of the inclusion, safety factor, its life span and the sequence of cleaning in the extraction block. Thus, at the safety factor of rocks of the non-ore inclusion less than 10–12, it is expedient to use the sublevel-chamber version of the development system, otherwise, the horizonal-chamber version.